Entomocomplex of onions in the Right-Bank Forest-Steppe of Ukraine - V. Kudla; G. Tkalenko; V. Ignat (Карантин і захист рослин)
Goal. To monitor the phytosanitary condition of onion crops in the Right-Bank Forest-Steppe of Ukraine and to establish the species composition of dominant pests.